Effect of Palm Fiber on Photo and thermo-degradation of Polyethylene composites - Smitthipong, Wirasak; Chollakup, Rungsima; Kongtad, Wuttinan; Delor-Jestin, Florence (Agriculture and Natural Resources, 2014)
Polyethylene/palm fiber composites (PEP) were prepared by blending low density polyethylene (PE) and palm fibers (diameter < 1 mm) in a twin-screw extruder. Thin films of PEP at 0–30% fiber weight were either exposed to accelerated artificial photo-ageing (λ > 300 nm, 60 °C) or to thermo-oxidation at 100 °C in an aerated oven. Infrared (IR) spectra after photo-oxidation showed that the incorporation of fibers in PE increased its degradation rate with the formation of carbonyl and vinyl groups. A decrease was observed in the aromatic C=C absorption IR peaks of the lignin structure in the PEP composites. This indicated that the lignin structure in the fibers was photo-oxidized and produced radical species for oxidation. Crystallinity change of the PEP composites, analyzed using differential scanning calorimetry, tended to increase upon photo- and thermo-ageing. This effect could be explained by chain scissions involved in the oxidation process, as the shorter chains of PE would have a higher mobility, allowing the reorganization of the PE matrix. Compared to thermo-degradation, the amount of vinyl groups remained constant indicating no reaction of the ketones in a Norrish type II process. The higher thermo-oxidation rate in PEP composites may be a result of radical species of cellulose and hemicellulose degradation in palm fibers.